Prepare and study the SrO additive on structural and electrical properties for Hg Ba2-x Srx Ca2Cu3O8+δ superconductor / Kareem Ali Jasim and Noor Qasim Fadhil - Jasim, Kareem Ali; Fadhil, Noor Qasim (2016)
In this paper, we study the replacing of Ba by Sr of for HgBa2-xSrxCa2Cu3O8+δ cuprate superconductor (x=0,0.1,0.2,0.3). The solid state reaction method will be used for forming samples. The X-ray diffraction analysis showed that prepared samples correspond to Hg-1223 phases with tetragonal structure. To find the critical temperature Tc, the measure electrical resistivity will be used by four-probe technique. It is shown that the Tc increase at addition of the Sr from 113K (x=0) to 138K (x=0.3).